An Ulnar-Type Dislocation of Fifth Carpometacarpal Joint: Case Report and Review of the Literature - Malshikare, Vijay A. (Journal of Hand and Microsurgery, 2019)
Unilateral pure dislocation of the fifth carpometacarpal joint (CMCJ) is a very rare injury. We are reporting the second case of an ulnar type of unilateral dislocation of a fifth CMCJ. Indian salutation (Namaskar) test and radiographs aid in diagnosis. Closed reduction and internal fixation by K-wires restored the normal anatomic relationships of the fifth CMC joint. This type of injury is prone to be missed in an emergency room due to soft tissue swelling, and particular attention should be paid to diagnose it in polytrauma patients. A review of the literature is presented.
Keywords: carpometacarpal joint; ulnar side dislocation; diagnosis; treatment